Public policy as a guarantee of early childhood rights in Colombia - Sánchez Cubides, Pedro Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this article is to analyze the national public policy of early childhood as a guarantee of the rights of children in Colombia. The method used was the consultation of the jurisprudence, doctrine, legal norms and documents that support the aforementioned policy. It was observed that public policy is not yet effective in guaranteeing the rights of early childhood, as there is still a lack of the serious commitment of the administration and interest on the part of some authorities, especially territorial ones. Similarly, there are advances in coverage, are advances in coverage, but not in quality and relevance. In addition, due to limitations in terms of financial resources of the State, comprehensive care is aimed at poor and vulnerable children, a situation that makes progress towards the universalization and progressivity of the rights of the this population difficult.